Evaluation of Feeding and Feed Utilization of Kuchi Indigenous Chicken Ecotype of Kenya - Chesoo, Ben K.; J , Kiptanui; J K , Kitilit; D K , Kios; G.W , Oduho, (African Journal of Education,Science and Technology (AJEST), 2018)
Kenya has a large diversity of indigenous chicken (IC) ecotypes. One of them is the Kuchi whose phenotypic attributes have made it popular in terms of high mature body weight. However, scanty information exists on the feed utilization of this IC ecotype. A study was carried out to evaluate the feed intake(FI), average daily gain(ADG) and the Feed Conversion Efficiency(FCE) of Kuchi IC growers fed with three levels energy diets: High(HE-2700MEKcal/Kg), Low(LE-2564.5MEKcal/Kg), and ground Maize Grain(MG); all managed under three feeding systems: Intensive(IS), Extensive(ES) and Extensive with Supplementation(ESS), on a two week change-over basis from week 12 to 17 of age. A Commercial ration under IS was utilized from day old to 11 weeks. A Randomized Complete Block Design (RCBD) was laid out for the experiment. Weekly growth weights on FI, ADG and FCE/Diet/System were recorded and means subjected to an ANOVA (SAS 2015) software tool. Results indicated that diets: HE (98.33g) and LE (93.88g) had significant (p<0.05) effect on the FI under ESS; LE (281.33g) was significant on the ADG, and the FCE (4.13) was significant under ESS on LE. It is concluded that the optimal growth of Kuchi IC is attained under a semi-intensive (ESS) and low energy ration (LE) respectively. It is therefore not economical to intensify the management of Kuchi IC ecotype. A Molecular characterization towards selection, breeding and local chicken genetic resource conservation to achieve an efficient feed utilization IC ecotype is recommended.